How Far a School Program Build Students’ Character? A CIPP Model Evaluation - Rahmiaty; Kamarullah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
The overarching objective of this research is to investigate a private boarding school’s character education program. Stufflebeam’s CIPP evaluation model served as the basis for the research, which covered the study’s context, input, process, and product. After administering a questionnaire to 35 second-year students, we compiled the necessary data through in-depth interviews with the principal and three teachers. The questionnaire was explored quantitively using regression analysis with a statistical application called SPSS statistics-25. Meanwhile, thematic analysis was utilized to analyze the qualitative data throughout condensation, and regression analysis from SPSS result to be used to conduct a quantitative investigation of the questionnaire. The qualitative data was analyzed using theme analysis throughout the condensation process, beginning with description, progressing through reduction, categorization, and interpretation of data. The results showed that the school positively affected students’ character development through the combination of academic and extracurricular programming. Similarly, pupils felt like they were making headway. Having full support from the institution, even from alums, is a massive plus for character-building programs. In return, the school gains the same merit, boosting the favorable profile of students so that the communities may recognize the school’s characteristics. A reciprocal advantage in developing students’ character is available between the school and the pupils.